Automating with Simatic S7-1200 : hardware components, programming with STEP 7 Basic in LAD and FBD, visualization with HMI Basic panels. - Berger, Hans, 1949- (Erlangen : Publicis, 2011)
The SIMATIC S7-1200 micro PLC offers a modular design concept with similar functionality as the well-known S7-300 series. Being the follow-up generation of the SIMATIC S7-200 the controller can be used in a versatile manner for small machines and small automation systems. Simple motion control functionalities are both an integral part of the micro PLC and an integrated PROFINET interface for programming, HMI link and CPU-CPU communication. With the Totally Integrated Automation (TIA) access, the engineering software Step 7 Basic offers a newly developed user interface, which is matched to intuitive operation. The functionality comprises all interests concerning automation: From configuring the controllers via programming in the graphics-oriented languages LAD (ladder diagram) and FBD (function block diagram) to program testing. The book presents the new hardware components of the automation system S7-1200, as well as its configuration and parameterization. A profound introduction into STEP 7 Basic illustrates the basics of programming and trouble shooting. Beginners learn the basics of automation with SIMATIC S7-1200 and advanced users of S7-200 and S7-300 receive the knowledge required to work with the new PLC.